Observation of positive and small electron affinity of Si-doped AlN films grown by metalorganic chemical vapor deposition on n-type 6H–SiC - 梁锋 陈平 赵德刚 江德生 赵志娟 刘宗顺 朱建军 杨静 刘炜 何晓光 李晓静 李翔 刘双韬 杨辉 张立群 刘建平 张源涛 杜国同 (Chinese physics B, 2016)
We have investigated the electron affinity of Si-doped AlN films（N_（Si）= 1.0 × 10~（18）–1.0 × 10_（19）cm~（-3）） with thicknesses of 50, 200, and 400 nm, synthesized by metalorganic chemical vapor deposition（MOCVD） under low pressure on the ntype（001）6H–SiC substrates. The positive and small electron affinity of AlN films was observed through the ultraviolet photoelectron spectroscopy（UPS） analysis, where an increase in electron affinity appears with the thickness of AlN films increasing, i.e., 0.36 eV for the 50-nm-thick one, 0.58 eV for the 200-nm-thick one, and 0.97 e V for the 400-nm-thick one.Accompanying the x-ray photoelectron spectroscopy（XPS） analysis on the surface contaminations, it suggests that the difference of electron affinity between our three samples may result from the discrepancy of surface impurity contaminations.